Behavior in operations management: Assessing recent findings and revisiting old assumptions - Bendoly, Elliot; Donohue, Karen; Schultz, Kenneth L. (Journal of Operations Management, 2006)
Abstract In this paper, we provide a perspective on why behavioral research is critical to the operations management (OM) field, what prior research exists, and what opportunities lie ahead. The use of human experiments in operations management is still fairly novel despite a small stream of publications going back more than 20 years. We develop a framework for identifying the types of behavioral assumptions typically made in analytical OM models. We then use this framework to organize the results of prior behavioral research and identify future research opportunities. Our study of prior research is based on a search of papers published between 1985 and 2005 in six targeted journals including the Journal of Operations Management , Manufacturing and Service Operations Management , Production and Operations Management , Management Science , Decision Sciences , and the Journal of Applied Psychology .